Effects of initial foot position on neuromuscular and biomechanical control during the stand-to-sit movement: Implications for rehabilitation strategies - Woohyoung Jeon; Ashley Dalby; Xuanliang Neil Dong; Chung-Hyun Goh (PLoS ONE, 2025)
Background Initial foot position (IFP) is one of the important movement strategies that influence neuromuscular and biomechanical control during sit-to-stand (STS) movements. Similarly, stand-to-sit (StandTS) is vital in rehabilitation settings for evaluating strength and balance control during descending movements. Understanding how IFP impacts changes in biomechanical and neuromuscular movement control factors during StandTS can provide valuable insights for designing effective rehabilitation programs. Methods Twelve healthy young adults participated in this study, examining three symmetric IFPs: (1) REF (reference); (2) wide: each foot was shifted outwards by 30% from REF; (3) TO (toes-out): symmetric toes-out angle of 30° from REF. Kinematic and kinetic differences among the three IFPs during StandTS were analyzed, along with the characteristics of muscle activation patterns using muscle synergy analysis. Results In the wide IFP, trunk flexion angle was reduced, and valgus angle was greater than in the other IFPs. The TO IFP resulted in greater dorsiflexion and knee flexion angles compared to the REF and wide IFPs. Compared to the REF IFP, both wide and TO IFPs showed greater eccentric work at the hip joint in the anterior-posterior (power absorption) and the vertical direction (gravitational force control) and demonstrated reduced postural sway in medio-lateral and vertical directions. Muscle synergy analysis of EMG activity revealed increased activation of back and plantar flexor muscle in the wide IFP, and increased contribution of hip joint muscles in the TO IFP. Conclusion The wide IFP increased the valgus angle, leading to reduced trunk flexion with increased back muscle activation. The TO IFP enabled greater angular displacement at the ankle and knee joints, enhancing hip joint muscle involvement in StandTS movement control. Both the wide and TO IFPs facilitated hip joint work, improving postural sway control during the descent phase of StandTS. These findings provide valuable insights for designing rehabilitation strategies tailored to specific patient needs.